50 keV H+ ion beam irradiation of Al doped ZnO thin films: Studies of radiation stability for device applications. (17th October 2017) - Sahoo, Susanta Kumar; Mangal, Sutanu; Mishra, D.K.; Singh, Udai P.; Kumar, Pravin
Abstract : Thin films of Al doped ZnO (Al:ZnO) were deposited on two substrates (Si and glass) at room temperature and 300°C using DC magnetron sputtering. These films were bombarded with 50 keV H + beam at several fluences. The pristine and ion beam irradiated films were analysed by X‐ray diffraction, Raman spectroscopy, scanning electron microscopy, and UV‐Vis spectroscopy. The X‐ray diffraction analysis, Hall measurements, Raman and UV‐Vis spectroscopy confirm that the structural and transport properties of Al:ZnO films do not change substantially with beam irradiation at chosen fluences. However, in comparison to film deposited at room temperature, the Al:ZnO thin film deposited at 300°C shows increased transmittance (from 70% to approximately 90%) with ion beam irradiation at highest fluence. The studies of surface morphology by scanning electron microscopy reveal that the ion irradiation yields smoothening of the films, which also increases with ion fluences. The films deposited at elevated temperature are smoother than those deposited at room temperature. In the paper, we discuss the interaction of 50 keV H + ions with Al:ZnO films in terms of radiation stability in devices.